Enhancing Crop Growth Efficiency through IoT-enabled Smart Farming System - Jadhav, Neda; B, Rajnivas; V, Subapriya; S, Sivaramakrishnan; Premalatha, S (EAI Endorsed Transactions on Internet of Things, 2023)
The agricultural sector is facing significant challenges in meeting the increasing demands for food production while ensuring sustainability and resource efficiency. To address these challenges, the integration of Internet of Things (IoT) technology into farming practices has gained attention as a promising solution. This research focuses on the development and implementation of an IoT-enabled smart farming system aimed at enhancing crop growth efficiency. The proposed system leverages IoT sensors and devices to monitor and collect real-time data on various parameters such as environmental conditions, soil moisture levels, and crop health. The collected data is then analyzed using advanced analytics techniques to gain valuable insights and make informed decisions regarding irrigation, fertilization, and pest control. By utilizing IoT technology, farmers can optimize their resource utilization, reduce waste, and maximize crop productivity. This research aims to investigate the potential benefits and challenges associated with implementing the IoT-enabled smart farming system. In this paper, a cutting-edge Internet of Things (IoT) technology is explored for monitoring weather and soil conditions for efficient crop development. The system was built to monitor temperature, humidity, and soil moisture using Node MCU and several linked sensors. Additionally, a Wi-Fi connection is used to send a notification through SMS to the farmer's phone about the field's environmental state. The results will help in developing strategies and guidelines for the widespread adoption of IoT-enabled smart farming practices, ultimately leading to sustainable and efficient crop production to meet the demands of a growing population.
Keywords: IoT; Node MCU; agriculture; sensors